(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to identify the role of in-service training courses in improving the teaching performance of history teachers in secondary school.And identify the differences between the answers of the search sample depending on the search variables(years of service –number of courses- Scientific qualification), the researcher adopted the descriptive and analytical curriculum and included the research sample (300) teachers and schools for the history material in secondary schools-Rusafa I.The resolution tool was built up of (40) paragraphs distributed in three areas (I:importance of training courses-II:teaching skills-III:obstacles of training courses), and the research reached the following results:-there are differences with statistical function between the averages of answers to the search resolution, attributed to the variable of training courses.- There are differences with a statistical function between the average answers to the search resolution attributed to the variable of the scientific qualification in favor of those who possess the qualification Bachelor’s degree-history, and the research reached a number of The most important conclusions are: reviewing in-service training programs for history teachers in secondary schools, as well as designing clear training programs and identifying the most important training needs for history teachers in secondary schools, in keeping with scientific developments and developments, and the most important research recommendations: providing educational tools and tools for history, especially maps and historical images, watching historical documentaries